Developing and testing a method for deformations measurements of structures. Issue 1 (2nd January 2017) - El-Ashmawy, Khalid L. A.
Abstract: Dynamic monitoring of structures is an important task in civil engineering that aims to determine the stability and safety of a structure by using information about its deformations. This paper describes the development of a method for the determination of structures deformations. The proposed method is developed to add a new solution to traditional methods of angle intersection and trigonometric leveling. It is designed to provide a simultaneous solution to all observations in one step using least squares solution to improve the expected accuracy and to generate the necessary data for statistical analysis. A practical experiment was made, where the observations of 7 deformation points on a simply supported steel beam with concentrated load were measured using the proposed method, total station and linear variable displacement transducers (LVDTs). Deflections measured directly from LVDTs were used as a reference for assessment of the serviceability of the beam. The results show that for the maximum deflection at mid-span of the beam, the differences between the measured deflections from LVDTs and proposed method are less than 0.87 mm corresponding to an error of 4.3%, while they are less than 1.32 mm causing an error of 12.5% for the case of total station measurements. Based on root mean square error values, the accuracy of point displacements determination using the proposed method is much better than total station measurements. The proposed method is suitable for the accurate determination of horizontal and vertical displacements and provides a realistic solution for monitoring structures at both entire structure and member levels.